2020
DOI: 10.1007/s12178-020-09640-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Operative Versus Non-Operative Treatment for Clavicle Fracture: a Systematic Literature Review

Abstract: Purpose of Review Operative and non-operative treatment of midshaft clavicle fractures seems to yield comparative functional results. Furthermore, it has been suggested that surgery is more expensive compared with non-operative treatment of clavicle fracture. Cost-effectiveness seems to be more important in trends of treatment decisions. The purpose of this study is to investigate the cost-effectiveness of clavicle fracture treatment. Recent Findings Seven publications were selected, and 5 studies showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Economic burden on society for medical treatments is continuously increasing and therapeutic options should be more and more evaluated with respect to the potential costs in relation the clinical functional results [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Economic burden on society for medical treatments is continuously increasing and therapeutic options should be more and more evaluated with respect to the potential costs in relation the clinical functional results [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…15-18 These include, in descending order of incidence, material irritation, nonunion, infection, or wound dehiscence. 40,41 In our literature review, only one study was unable to demonstrate an effect of smoking on postoperative complications. 10…”
Section: Discussionmentioning
confidence: 85%
“…41 They emphasize in particular that reoperations are associated with poorer functional results and higher healthcare costs. 40…”
Section: Discussionmentioning
confidence: 99%
“…The prior studies comparing operative with nonoperative management of displaced midshaft clavicle fractures have demonstrated mixed results. Five of the 7 studies comparing the cost-effectiveness of operative and nonoperative management that were included in a systematic review by Kask et al found that operative management was more expensive overall 44 . Liu et al, on the other hand, found that operative management was more cost-effective at a WTP threshold of $50,000 per QALY 31 .…”
Section: Discussionmentioning
confidence: 99%